Markets of Good Intentions: Constructing and Organizing Biogas Markets Amid Fragility and Controversy - Adam Buchhorn (Copenhagen Business School (CBS), 2010)
This research project examines markets for biogas plants in Denmark, referred to simply as biogas markets, as a fragile and controversial process of framing and organizing by analyzing how unexpected events, called `overflows', and controversies influence how markets frame biogas plants as a valuable economic good and ensure biogas plants are implemented through market transactions. Without well-constructed and well-organized markets these fundamental economic functions cannot take place. The overarching argument of the project is that to realize changing technical, political, and socio-economic intentions of biogas the market must be framed and organized to reframe and solve overflows and controversies that characterize biogas markets in Denmark. Otherwise, what we end up with are `markets of good intentions'. Although they are rarely predicted and constitute the robustness as well as the source of the inevitable fragility and controversy of the market, it is essential to the framing of biogas plants as a valuable commodity and the completion of transactions, that overflows and controversies are addressed and internalized into the market assemblage. This involves identifying and rendering them debatable based on the calculations and other elements that underpin the alleged value of biogas and the actions of market actors...
hdl:10398/8048
Keywords: 650